EXPLORING THE POTENTIAL OF 3D PRINTING IN PHARMACEUTICAL DEVELOPMENT - KURIL, ANJALI; AMBEKAR, ANJU; NIMASE, BHARATI; GIRI, PRACHI; NIKAM, PRAJWAL; DESAI, HARITA; AHER, SHUBHANGI (International Journal of Current Pharmaceutical Research, 2023)
Pharmaceuticals have been transformed by additive manufacturing, often known as three-dimensional printing (3DP) a disruptive technology. The concept of additive manufacturing is examined, with a focus on its potential for quick prototyping, cost savings, and development of customized medicines. In the pharmaceutical industry 3DP is used to develop numerous dosage forms and drug delivery systems including oral films, controlled-release tablets and transdermal patches. It also makes it possible to produce specialized medical prosthetics, implants and gadgets. The applications of various 3DP types such as material extrusion, material jetting, binder jet printing and powder-based procedures like selective laser sintering, are thoroughly covered. This review assesses the compatibility of the common 3DP materials for pharmaceutical applications including hydroxypropyl methylcellulose, hydroxypropyl cellulose, Carbopol and Eudragit. This review article forecasts 3DP prospects and shortcomings. The technology's continued development and use in the pharmaceutical industry and other industries will depend on overcoming regulatory challenges, creating standardized procedures and optimizing material alternatives. By tackling these issues 3DP has a great deal of potential to revolutionize personalized medicine, medical device production and variety of other industries ultimately leading to better patient outcomes and healthcare solutions. Types and principles, materials, applications, scalability, regulatory compliance and potential future challenges are discussed in this review paper.